Regarding the 33/11KV substation (external substation) and temporary substation (internal substation) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the 33/11KV substation (external substation) and temporary substation (internal substation) of BRACU new campus project.